IMAGES OF LEGAL HUMANISM - Osler, Douglas (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 2001)
Legal humanism is an expression generally used to refer to the study of Roman law by 16th Century philologists. Coming a century an a half after what is generally taken to be the birth of humanism, it is generally understood to be part of humanism mostly in its interest for the historical interpretation of Latin texts rather than for participating in the value orientation of humanism. Strangely enough, legal history has taken the philological work of legal humanism for granted not seeing that legal humanism was itself inscribed in history. First, we should note that when it was being developed in the 16th Century, this philological work in Roman law was marginal if one compares publications in that field to publications of medieval Italian jurisprudence. Secondly, legal history has tended to diminish the presence of interpretation in the work of legal humanists who probably more than is generally acknowledged adapted to their times the Latin texts inventing values which have nothing to do with the Roman sources. Legal humanism has never been used to mean the legal aspects of humanitarianism and probably needn’t to be. If the work of interpretation of Roman law has opened some windows into humanistic values, Roman law itself was the codification of an unjust power structure.